2015
DOI: 10.5507/bp.2013.026
|View full text |Cite
|
Sign up to set email alerts
|

Arthrocentesis of the temporomandibular joint: A review

Abstract: Background. Arthrocentesis is a very gentle method for lavage of the joint space. The principle consists in the introduction of a pair of needles into the upper joint space and subsequent lavage using physiological saline or Ringer's solution. Arthrocentesis of the temporomandibular joint is used in both cases of acute closed lock and treatment of various temporomandibular disorders. Methods. A literature search in Pubmed database, using key words: Temporomandibular joint (TMJ), Arthrocentesis, indications, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 32 publications
0
50
0
17
Order By: Relevance
“…This includes perforation of the external auditory canal, the occurrence of blood clots in the external auditory canal, tympanic membrane injuries, partial hearing loss, a feeling of a blocked ear and dizziness. 1,12 In this study facial paralysis were observed in 8, fluid extravasation in 7, dizziness in 2, bleeding due to temporalis superficial artery injury in 5 cases. In conclusion TMJ arthrocentesis is a method that is less invasive compared to other surgical methods and arthroscopy.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…This includes perforation of the external auditory canal, the occurrence of blood clots in the external auditory canal, tympanic membrane injuries, partial hearing loss, a feeling of a blocked ear and dizziness. 1,12 In this study facial paralysis were observed in 8, fluid extravasation in 7, dizziness in 2, bleeding due to temporalis superficial artery injury in 5 cases. In conclusion TMJ arthrocentesis is a method that is less invasive compared to other surgical methods and arthroscopy.…”
mentioning
confidence: 59%
“…The frequency of these complications mentioned in the literature rangesbetween 2% and 10%. 12 The potential complications of arthrocentesis are infection, external auditory canal perforation, fluid extravasation into the soft tissues, bite change, skuffing of the cartilage of the TMJ, and hematoma. 13 Temporary facial paresis or paralysis caused by the use of a local anesthetic, or swelling of the neighboring tissues caused by perfusion of Ringer's solution may occur during arthrocentesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TMB başta çene eklemi olmak üzere, çiğneme kaslarını ve pek çok anatomik yapıyı etkiler. TMB karakteristik semptomları ağrı, çene hareketlerinde bozulma ve bu hareketler sırasında ortaya çıkan klik sesidir (2,12,13) . TMB hastalıklarında birçok faktör suç-lansa da ciddi olgularda etiyoloji kompleks ve multifaktöriyeldir (8) .…”
Section: Discussionunclassified
“…В течение последних 15 лет в челюстно-лицевой хирургии и стоматологии получили бурное развитие как консерватив-ные, так и хирургические методы лечения ВНЧС, в том чис-ле с использованием малоинвазивных вмешательств [5][6][7]. Особый интерес представляет хирургическое лечение бо-лезней ВНЧС у пациентов с ревматическими заболевания-ми (РЗ).…”
unclassified